Double Carrier Pulse width Modulation Control for a Quasi Impedance Source Inverter - Akrami, Amin; Gitizadeh, Mohsen; Nayeripour, Majid; Ghaderi, Mohammad (Electrical, Control and Communication Engineering, 2011)
The quasi-Z-source inverter (QZSI) is similar to the ZSI. The QZSI has been developed which feature several improvements and no disadvantages when compared to the ZSI. Also Double carrier pulse width modulation control is a new control method for controlling the ZSI and it has a lot of benefit if to compare with other traditional control methods. This paper improved properties of the QZSI by using the double carrier pulse width modulation control. Simulation results will be presented to demonstrate the new features.